Study of Thermal Conductivity and Mechanical Property of Insulating Firebrick Produced by Local Clay and Petroleum Coal Dust as Raw Materials. (2015) - Rahman, Md. Hamidur; Islam, Md. Tariqul; Minhaj, Tamzid Ibn; Azad, M.A.K.; Hasan, Md. Mehedi; Haque, A.A. Md. Rezaul
Abstract: Thermal insulation is one of the major requirements for various industrial applications. In this study the evaluation of thermal conductivity and mechanical property of an insulating refractory was carried out at elevated temperature. As additive, coal dust and 4-5wt% water were mixed with local clay. After forming the bricks by conventional uniaxial pressing method, the samples were first air dried for 2 hours at ambient temperature of 30 °C, then oven dried for 8-10 hours at 110 °C and finally fired in furnace for 6 hours at 1050 °C. The combustion of fully combustible coal incorporated extra porosity in the final products resulting in enhanced thermal insulation. As experimental variables, three different sets of coal particle size range (coarse: 100-500 μm, medium 20-100 μm, fine: less than 20 μm) and four different coal percentages were used. The results thus obtained showed that increased fineness of coal dust for a fixed coal percentage improved crushing strength and porosity and decreased thermal conductivity. In contrast, for a fixed coal particle size range, crushing strength and thermal conductivity decrease and the percentage of porosity increases with the increase of coal percentage.